Small business taxation:an evaluation of the role of special treatment policies - Pope, Jeffrey (School of Economics and Finance, Curtin Business School, 2008)
In many countries small businesses expect and generally receive special treatment, concessions or arrangements regarding taxation compared with medium and large business. Such policies are based primarily upon the role and importance of small business in economic growth and especially job creation, and the high administrative and compliance costs of including a large number of small entities in the tax system. This paper focuses on the latter aspect, using examples and data from various countries in the world, particularly the UK, USA, New Zealand and Australia. The arguments for special treatment seem compelling, particularly lower administrative and compliance costs, although difficulties usually arise at the margin or threshold where the special treatment ends. However, an often neglected argument is that small business often engage in high levels of tax evasion, based on the so-called ?cash economy?, an opportunity generally denied to large business (at least domestically). It can be argued that benefits arising from evasion roughly approximate to the higher compliance costs endured by small business, particularly for income taxation. This paper evaluates this argument and the extent that special treatment taxation arrangements of small business are warranted. The conclusion sums up the experiences of the countries considered, the key policy implications, the limitations of the analysis, and indicates areas for further research.